HUBUNGAN FATHERLESS DENGAN JUVENILE DELIQUENT PESERTA DIDIK KELAS XI DI MAN 1 PASAMAN BARAT - Lhatifah Syawitha; Besti Nora Dwi Putri; Rahmawati Wae (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Children who experience fatherlessness tend to have low self-esteem, emotional disorders, and are prone to showing deviant behavior or juvenile delinquency. This study aims to: 1) Describe the Fatherless students of MAN 1 Pasaman Barat, 2) Describe the Juvenile Deliquent students of MAN 1 Pasaman Barat, 3) Determine the Relationship between Fatherless and Juvenile Deliquent students at MAN 1 Pasaman Barat. This study uses a correlation research type. The population of this study were 230 students in class XI Phase F at MAN 1 Pasaman Barat and a research sample of 50 people using purposive sampling techniques. The instrument used was a questionnaire. The data analysis technique used was the Pearson product moment correlation. The results of the study indicate that: 1) fatherless students at MAN 1 Pasaman Barat are in the high category, 2) juvenile delinquent students at MAN 1 Pasaman Barat are in the low category, 3) there is a relationship between fatherless and juvenile delinquent students at MAN 1 Pasaman Barat. BK teachers can also provide targeted counseling services for students who experience fatherlessness by conducting early identification and an in-depth approach in order to help students manage their emotions and direct them in a positive direction.